Lactate Dehydrogenase as A Potential Prognostic Biomarker in Subarachnoid Haemorrhage: A Systematic Review - Yang Yang Endro Arjuna; Alexander Erick Purnomo; Jeremiah Hilkiah Wijaya; Mary Christina Elsa; Yusak Mangara Tua Siahaan; Made Agus Mahendra Inggas; Randra Frits Christopher; Michelle Gloria Setiawan; Haddiyya Wardhani Nugroho (Universitas Pelita Harapan, 2025)
Background: Subarachnoid haemorrhage (SAH) lacks specific prognostic blood markers, but lactate dehydrogenase (LDH), linked to cellular damage, shows potential for predicting adverse outcomes in SAH patients. Elevated LDH levels may reflect anaerobic metabolism and tissue injury following SAH, providing insight into disease severity and complications. This review explores the relationship between lactate dehydrogenase levels and outcomes in SAH patients. Method: A systematic review was conducted using PubMed, Europe PMC, ScienceDirect, and Google Scholar, searching for terms like